Understanding platelet thrombogenicity cascade of the biocompatible chitosanderivates in von willebrand disease - Saad, Arman Zaharil Mat (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2016)
Introduction: Chitosan extracted from the shells of arthropods have becoming one of the most promising local hemostatic agents because it is of particular interest as it functions independently on platelets and normal clotting mechanisms. Objectives: This work verified the underlying mechanisms of chitosan-induced platelet thrombogenicity cascades and comprises experimental tests such as degradation ability; coagulation analysis and the investigations of hemostatic mediators: von Willebrand Factor (vWF), Factor 8 (FVIII), Thromboxane A2 (TXA2), P2Yl2, glycoprotein IlbIIIa (GpIIbIIIa), Transforming Growth Factor- Beta 1 (TGF-~1) and Platelet Derived Growth Factor-AB (PDGF-AB) in normal donors and von Willebrand disease (vWD) patients in vitro. Materials and Methods: Comparative studies have been conducted to measure the hemostatic capacity of biodegradable: 7% N,O-Carboxymethylchitosan (NO-CMC) (with 0.45 mL collagen), 8% NOCMC, Oligo-chitosan (0-C) and 0-C 53. Lyostypt, the topical hemostatic agent was used as a positive control. This study was conducted using scanning electron microscope, enzyme-linked immunosorbent assay, westergren, coagulation analyzer, western blotting and flow cytometry techniques. Fourteen vWD and normal subjects were recruited in this study with provided informed written consent. Results and Discussions: 0-C type of chitosans are able to enzymatically degrade, 1 possess better porosity and the scaffold pores are sufficient to allow nutrients and cells to enter and by encouraging platelet activities to accelerate hemostasis and wound healing process. 0-Cs exert a combined effect on thrombogenesis by causing platelets to adhere, activate, aggregate and forms insoluble fibrin network to strengthen platelet plug formation by elevating the studied mediators.O-C was capable to induce the expression levels of vWF, FVIII and TXA2 receptor signals. This signaling pathway assists the platelet aggregation. Also, GpIIbIIIa and P2Y 12 analysis showed that 0-C group of chitosan are capable of activating platelets by providing a good surface for blood hemostatic mediators and signals to facilitate thrombin generation. 0-C-activated platelets lead to the release of growth factors, mainly TGF-~1 and PDGF-AB. Therefore, this exhibited that greater expression level of 0-C group of chitosan assists in mediating wound healing process. Conclusion: Tested chitosan-stimulated-mediators potentially initiate the platelet actions and expedite the hemostasis processes in vitro. Based on the outcome of this research, the 0-C and 0-C 53 stimulated hemostasis process and worked better and equal to the commercially available lyostypt in normal donors or subjects and vWD patients in vitro.